Comparative coleoptera fauna study (Insecto: Coleoptera) in two environments of a colombian tropical rain forest - CAMERO-R., EDGAR (Revista Colombiana de Entomología, 1999)
Coleoptera fauna in a Colombian rain forest was cómpared in gaps and undisturbed forest. Five replicas in each site were studied through pitfall traps to catch its insects. Samples were determined until the family level, and the Margaleff index was used to determine family riches. Homogeneity between samples was compared and between sites through statistical tests in its rich indexes. Statistic significant differences between samples and bet-ween sites were-t found, but differences in Coleoptera fauna composition in sites were registered.